ISSUES AND CHALLENGES OF TECHNOLOGY USE IN INDONESIAN SCHOOLS: IMPLICATIONS FOR TEACHING AND LEARNING - Mali, Yustinus Calvin Gai; Kurniawan, Daniel; Januardi, Josephine Ilona; Swara, Sanditya Jati; Lokollo, Natalia Christy Emy; Picauly, Irma Amy; Paramitha, Nathasa Gracia; Tanore, Jose Argo; Dewani, Meta Sekar; Pakiding, Risdy Wijaya (Sanata Dharma University Yogyakarta, 2023)
This paper mainly aims to explore issues and challenges in using technology to support teaching and learning in various schools located on three different islands in Indonesia, such as in Kalimantan, Nusa Tenggara, and Papua islands. The exploration was done through a holistic literature review of 30 national and local newspapers and online articles relevant to the aim of the study. We performed a peer-debriefing activity to present our review analysis to each other, comment on it, and made necessary revisions to our analysis to ensure the credibility of our review. While the results communicated various things, we could highlight some commonalities: unequal distribution of technology support or facilities in schools, creative ways to support teaching and learning practices regardless of the very minimum facilities that schools have, and continuous support from the Indonesian government and private sectors to improve school technology-supported facilities. We then discussed those commonalities in light of the relevant literature and their implications for teaching and learning to benefit school teachers or educational practitioners planning to teach in schools outside Java with minimal technological-related school facilities.